FAKTOR- FAKTOR YANG MEMPENGARUHI PENCEGAHAN KEJADIAN DROP OUT TUBERKULOSIS PADA KELUARGA DI SELURUH WILAYAH KERJA PUSKESMAS KOTA SEMARANG - Dita Aulia Ramadhayanti; Kusyogo Cahyo; Laksmono Widagdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Incidence Drop Out tuberculosis in the city of Semarang increased, in 2015 with the number of smear positive TB cases as many as 8226 cases of drop out tuberculosis and an increase in the next year that is in 2016 with the number of smear positive TB cases as much as 3175 with the number of incidents drop out tuberculosis as many as 142 scattered in 37 working area of puskesmas in Semarang city. Drop out tuberculosis is a patient who has been treated and dropped out of treatment 2 months or more with a positive smear. This study aims to analyze the role of families against the prevention of drop out TB events. This research is a quantitative research with cross sectional approach by using Propostional sampling technique got sample of 72 families from pemudianita TB twirulan I and II in all working area of Semarang city health center. Data collection was done through interview with questionnaire. Data analysis is done univariat and bivariate. The result of the research showed that the factors that influence the family to prevent the drop out of tuberculosis are influenced by some variables (p = 0,001), susceptibility (p = 0,001), self efficacy (p = 0,012).